Metabolomics analysis reveals Oct4 overexpression drives metabolic reprogramming and enhanced glycolysis and pentose phosphate pathway in lung adenocarcinoma cells. (21st March 2022) - Tang, Yabin; Zhu, Liang; Chen, Hongzhuan; Meng, Shuang
Abstract: Poor prognosis in the underlying mechanisms involved in lung adenocarcinoma and its treatment leads to low survival rates in patients. Emerging evidence indicates that cancer is primarily a metabolic disease and metabolic reprogramming is a well‐established hallmark and driving force of cancer. Oct4, acting as an oncogene, is a major regulator of cell pluripotency. It can reprogram the differentiated cells into cancer stem cells (CSCs) and plays an oncogenic role when pathologically hijacked. However, data that Oct4, the genetic reprogramming factor, could induce metabolic reprogramming have been very limited, and the direct evidence in metabolic level whether Oct4 reprograms metabolome is lacking. In the present study, integrated untargeted and targeted metabolomics analyses were utilized to investigate metabolic changes induced by Oct4 overexpression in lung adenocarcinoma cells. The results suggested that elevated expression levels of Oct4 drive metabolic reprogramming. Oct4 overexpression redirects glucose catabolism to glycolysis pathway and to the oxidative pentose phosphate pathway (PPP). This study identifies unique pathways that are candidate therapeutic targets for the treatment of lung adenocarcinoma. This study also aims to improve our understanding of the cancer‐promoting activity of Oct4 and help identify novel diagnostic and therapeutic strategies for cancer treatment.